Effect of forced convection on the formation of the as-cast structure and macrosegregation of Sn-10wt.% Pb alloy: A numerical study. (July 2023) - Zhang, Zhao; Wu, Menghuai; Zhang, Haijie; Ludwig, Andreas; Kharicha, Abdellah
Highlights: Importance of crystal remelting during alloy solidification. Role of TMF in promoting the equiaxed grain formation through crystal fragmentation. Formation mechanism for the as-cast structure and macrosegregation under the effect of TMF. A refined three-phase mixed columnar-equiaxed solidification model considering TMF. Abstract: A series of solidification benchmark experiments based on Sn-10wt.% Pb alloy were performed at the SIMAP Laboratory in Grenoble, France (Hachani et al., 2015) to study the effect of different types of forced convection on the as-cast structure and macrosegregation. Forced convection was achieved by using a traveling magnetic field (TMF). Four cases were investigated: without TMF; TMF in the same direction as natural convection; TMF in the opposite direction as natural convection; and TMF periodically reversed with respect to natural convection. In the current study, a three-phase mixed columnar-equiaxed solidification model was used to "reproduce" the above experiments to understand the flow effect on the as-cast structure formation. The dendrite fragmentation is regarded as the only source of equiaxed grains. Remelting/destruction of equiaxed grains in the superheated melt is considered. The continuous growth of the surviving equiaxed grains and further competition with the as-developed columnar dendrites, leading to columnar-to-equiaxed transition (CET), are included. Except for Case III (i.e., a TMF in the opposite direction as natural convection), satisfactory simulation-experiment agreements in terms of the temperature field, as-cast structure and macrosegregation are obtained for the remaining three cases. Based on the simulation results, it is found that 1) TMF plays an important role in homogenizing the temperature field and promoting the formation of equiaxed grains via fragmentation, consequently facilitating the appearance of CET; 2) TMF tends to generally intensify macrosegregation and increase the number of channel segregations; and 3) the simultaneous solidification/remelting process represents a significant species/energy transport mechanism. Ignoring the remelting of equiaxed grains would lead to an overestimate of the local temperature in the remelting zone. The reason for the mismatch between the simulation and experimental results obtained for Case III is discussed.